Digestive physiology of pigs [ proceedings of the 8th symposium - Lindberg, J. E. [ (Jan E.)] (CABI, 2001)
This text brings together edited and revised papers presented at the 8th Symposium on Digestive Physiology in Pigs held in Uppsala in June, 2000. It contains papers from leading scientists from around the world in this subject.